2010
DOI: 10.1111/j.1749-6632.2010.05454.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anthropogenic global changes on immune functions and disease resistance

Abstract: Humans are changing the environmental conditions of our planet, and animal immune functions are being affected by these modifications. For instance, a diversity of chemical contaminants is entering ecosystems and modifying immune functions directly or indirectly through altered host-parasite interactions. Also, global temperature changes have caused outbreaks of disease that have decimated and even extirpated some host species, outcomes partially driven via immune alterations. Finally, some invasive species ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
193
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(197 citation statements)
references
References 233 publications
(266 reference statements)
4
193
0
Order By: Relevance
“…Of the tested climate-based hypotheses for Atelopus declines, only the climate-variability hypothesis was supported here, consistent with previous findings that temperature variability compromises amphibian immune defenses (32) and that disease outbreaks frequently occur during extreme temperature events (33). Increases in climate variation are often linked to increases in the intensity and frequency of extreme events, which are projected to increase with anthropogenic climate change (1).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Of the tested climate-based hypotheses for Atelopus declines, only the climate-variability hypothesis was supported here, consistent with previous findings that temperature variability compromises amphibian immune defenses (32) and that disease outbreaks frequently occur during extreme temperature events (33). Increases in climate variation are often linked to increases in the intensity and frequency of extreme events, which are projected to increase with anthropogenic climate change (1).…”
Section: Discussionsupporting
confidence: 74%
“…Finally, there is the climate-variability hypothesis, which proposes that temporal variability in temperature partially drives amphibian disease dynamics (32), although temperature variability could contribute directly to declines as well. This hypothesis is partly based on observations that disease outbreaks are often associated with extreme temperature events (33) and partly on evidence that temporal variability in temperature can cause suboptimal immunity in amphibians, potentially increasing their susceptibility to Bd or other infections (32). Many components of amphibian innate and adaptive immune systems depend on external temperature, but it takes time for amphibians to adjust these systems to temperature changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our findings of relatively normal transcription of AHR, Bodkin et al (2012) indicated that average annual oil encounter rates ranged from 2 to 24 times yr −1 for females, and 2 to 4 times yr −1 for males. Mitigation of detrimental effects imposes demands on animals above those normally required to sustain life and may result in reduction of fitness evidenced by decreased reproductive capability, increased susceptibility to disease, or disadvantageous behavioral changes (Graham et al 2010, Martin et al 2010. Such effects may ultimately be manifested in reduced survival rates , Monson et al 2011) that contributed to the delayed recovery of sea otters observed in areas of PWS initially oiled in 1989 (Bodkin et al 2002).…”
Section: Statistical Clustersmentioning
confidence: 99%
“…However, significant knowledge gaps remain in wildlife immunology including lack of basic species-specific data and outstanding questions surrounding factors that influence immune responses and infection patterns [2,4]. The relationship between immune function and infection has rarely been examined in wildlife despite suggestions that these processes play a part in health, population decline and extinction [5][6][7].…”
Section: Introductionmentioning
confidence: 99%